Distribution of carbon and nitrogen along hillslopes in three valleys on Herschel Island, Yukon Territory, Canada - Ramage, Justine L.; Fortier, Daniel; Hugelius, Gustaf; Lantuit, Hugues; Morgenstern, Anne (CATENA, 2019)
Thermokarst results from the thawing of ice-rich permafrost and alters the biogeochemical cycling in the Arctic by reworking soil material and redistributing soil organic carbon (SOC) and total nitrogen (TN) along uplands, hillslopes, and lowlands.Understanding the Impact of this Redistribution is key to better estimating the storage of SOC in permafrost terrains. However, there are insufficient studies quantifying long-term impacts of thaw processes on the Distribution of SOC and TN along hillslopes.We address this issue by providing estimates of SOC and TN stocks along the hillslopes of three valleys located on HerschelI sland (Yukon, Canada),and by dicussing the impact of hillslope thermokarst on the variability of SOC and TN stocks. We found that the average SOC and TN 0–100cm stocks in the valleys were 26.4 ± 8.9kg C m-2 and 2.1 ± 0.6kgNm-2. We highlight the strong variability in the soils physical and geochemical properties within hillslope positions. High SOC stocks were found at the summits, essentially due to burial of organic matter by cryoturbation, and at the toeslopes due to impeded drainage which favored peat formation and SOC accumulation. The average carbon-to‑nitrogen ratio in the valleys was 12.9, ranging from 9.7 to 18.9, and was significantly higher at the summits compared to the backslopes and footslopes (p < 0.05), suggesting a degradation of SOC downhill. Carbon and nitrogen contents and stocks were significantly lower on 16% of the sites that were previously affected by hillslope thermokarst (p < 0.05). Our results showed that lateral redistribution of SOC and TN due to hillslope thermokarst has a strong impact on the SOC storage in ice-rich permafrost terrains.